Prevalence of hereditary transthyretin cardiac amyloidosis (mATTR) in Western Denmark. (25th November 2020) - Rasmussen, T.B; Vase, H; Ladefoged, B; Dybro, A.M; Clemmensen, T; Terkelsen, A.J; Molgaard, H; Petersen, L.N; Poulsen, S.H
Abstract: Purpose: To investigate the prevalence of mATTR in a cohort of consecutive ATTR patients in a tertiary Danish Amyloidosis Center. Methods: Consecutive patients in the period from 2001 to 2019 with a definite diagnosis of ATTR-CA or ATTR-FAP based on either 99-Tc-DPD-scintigraphy, or transthyretin deposition in the myocardium or fatty tissue proved by immunohistology or protein mass spectrometry underwent testing for exonic genetic TTR variants. The distributions of age at time of diagnosis of mATTR and wildtype ATTR (wtATTR) are described by mean age, standard deviations, and range. Results: Seventy-four caucasian patients of Danish ancestry except one (Swedish) with ATTR were included (72 ATTR-CA, 2 ATTR-FAP). TTR missense variants were present in 13.5% (10/74) of ATTR patients concluded to have mATTR: c.148G>A/p.Val50Met, n=1; c.187C>T/p.Pro63Ser, n=1; c.193G>T/p.Ala65Ser, n=2; c.218G>C; p.Gly73Ala, n=1; c.391C>A/p.Leu131Met, n=3; c.424G>A/p.Val142Ile, n=2. The mean age of mATTR patients was 57.6 years ±13.0, range 37.1–71.3 years, and was significantly lower than mean age for wtATTR patients: 79.4 years ±5.5, range 65.7–90.2 years, p=0.0004 (Welch's two-sample t-test with unequal variances). All patients with mATTR had familial disease proven by clinical phenotyping of family members or had a positive family history with heart failure and pacemaker use. Conclusion: A minority of Danish patients (10–15%) with ATTR have mATTR. These mATTR patients are characterised by a significantly younger age at time of diagnosis than wtATTR patients. This observation indicates that TTR gene test may not be necessary in ATTR in patients older than 75 years. For the first time, the p.Val142Ile TTR variant, associated with mATTR and prevalent in 4% of African-Americans, was identified in a Danish family with mATTR-CA – a finding that may be explained by a common founder effect. Funding Acknowledgement: Type of funding source: None